The Meaning of Family's Adaptation Experiences Among Schizophrenia Caregivers in the Tidal Flood Areas in Indonesia: A Phenomenology Study - Eka Budiarto M.Kep., Sp.Kep.J; Mustikasari SKp., MARS (SAGE Publishing, 2024)
Introduction Caring for patients who have schizophrenia in tidal floods requires more effort than patients who have schizophrenia in non-tidal flood areas. Family caregivers are required to manage stress and burden through adaptation to roles and the environment. Objective The purpose of this study was to explore the meaning of family adaptation experiences of those who care for patients with schizophrenia in a tidal flood area. Methods This research is a qualitative research with a descriptive phenomenology. The sampling technique used purposive sampling, and the number of participants was 10. The data collection used in-depth interview techniques. The Colaizzi method was used to analyze data. Results The adaptation experience meaning of family caregivers obtained four themes: (1) forms of family caregiver responses; (2) patient engagement as a way to provide quality care at home by family caregivers; (3) family caregivers' difficulties in utilizing health services; and (4) resources for family caregivers. Conclusion The meaning of adaptation is whether the family caregivers feel the impact of their role and have difficulty utilizing health services in caring for patients. Despite this, family caregivers still try to continue to involve patients in daily activities and look for sources of support that are useful for them. Recommendation The physical and psychological well-being of family caregivers also need to be improved to support optimal care for patients who have schizophrenia by family caregivers at home.